Belait Language Maintenance in Brunei Darussalam (International Journal of Linguistics and Indigenous Culture, 2025)
The Belait language, an endangered indigenous language of Brunei, is experiencing a significant decline due to language shift, urbanization, and reduced intergenerational transmission. This study provides a descriptive analysis of the current status of Belait, examining the sociolinguistic factors contributing to its endangerment and evaluating strategies for its preservation. Findings indicate that Belait faces challenges such as the dominance of Malay and English, limited institutional support, and a sharp decline in fluent speakers. However, community-led revitalization projects, linguistic documentation, and digital initiatives have emerged as crucial interventions to mitigate this decline. Government-supported language documentation efforts, integrating Belait into digital platforms, and community-driven educational programs have been identified as key strategies for sustaining the language. This study underscores the urgent need for structured institutional support and policy driven initiatives to complement grassroots efforts, ensuring the survival of Belait as a vital component of Brunei’s linguistic and cultural heritage. Strengthening language maintenance strategies through education, digital engagement, and government collaboration is essential to reversing the trend of language loss for future generations.